Pengaruh Komunikasi Terapeutik Perawat Terhadap Kepuasan Pasien di Rawat Jalan RSUD Jogja - Mahendro Prasetyo Kusumo (Universitas Muhammadiyah Yogyakarta, 2017)
The Objective of this study is to know influence of nurse therapeutic communication to satisfaction of patients satisfaction in RSUD Yogyakarta. The study was a quantitative research methods such as surveys of descriptive inferential research with cross sectional approach. Number of samples in this research is 285 sample in inpatient and 140 in emergency room. The instrument used a questionnaire. Analysis of data using multiple linear regression. This study show that there is the influence of therapeutic communication nurse to satisfaction of outpatients and Emergency room in RSUD Yogyakarta, and orientation phase is a phase that most influence on patient satisfaction. The most influential to therapeutic communication is termination stage.